Prevalence of zoom fatigue and associated factors among students of the health area of the state of Ceará, Brazil (Research, Society and Development, 2022)
The Covid-19 pandemic brought to the world a need to adapt our lives to a new reality, this fact caused different types of impacts in the most diverse areas. The field of education was one of those that underwent the greatest transformation. The aim of the present study was to investigate the prevalence of zoom fatigue and associated factors among health students in the state of Ceará, Brazil. This is a cross-sectional study carried out with 781 students from different courses in the health area. The Zoom Exhaustation & Fatigue Scale (ZEF) English version was used with the questions currently validated for Brazilian Portuguese. Of the total number of respondents, 68.9% were female with a mean age of 23.3 ± 5.45 years. Among those who participated, 85% (664) experienced zoom fatigue. When comparing the two groups regarding the practice of some hobby, there was statistical significance (p=0.0045) for those who did not experience zoom fatigue. As for the practice of physical activity, a significance of p=0.004 was found. As for the ZEF questionnaire, it was noted that in all parameters evaluated there was statistical significance (p